PENGARUH FAKTOR DEMOGRAFIS TERHADAP PERILAKU PEMILIH KARENA POLITIK UANG PADA PEMILU 2024 DI KECAMATAN SEMARANG SELATAN DAN KECAMATAN SEMARANG TIMUR KOTA SEMARANG - Nanda Lintang Tyas Pratiwi; Fitriyah Fitriyah; supratiwi supratiwi; Hary Gunarso (Journal of Politic and Government Studies, 2026)
This research was conducted to examine the influence of demographic factors (independent variables) on voter behavior due to money politics (dependent variable) in the 2024 election in South Semarang District and East Semarang District, Semarang City. Money politics is a phenomenon that often occurs in Indonesia ahead of general elections. Money politics is a form of dishonesty in elections. The form of dishonesty in money politics is reflected through the giving of money, goods, or assistance with the aim of obtaining voter support from the community, and this is done with the intention of influencing the number of votes for a particular candidate so that the chances of winning the election votes are greater. This research focuses on voter behavior analyzed using a demographic factor approach, which includes age, gender, education level, income level, and occupation to see how voter tendencies respond to money politics using a quantitative approach.This research is a type of quantitative study with primary data obtained through the results of questionnaires distributed to respondents who have the right to vote in the 2024 election. The sampling technique used in this study is Multistage Random Sampling. The data analysis techniques used in this research include validity tests, reliability tests, and simple regression tests to determine the influence between demographic factors and voter behavior. The findings of this study indicate that demographic characteristics with certain traits tend to be more vulnerable to the practice of money politics.The research results show a significant influence of demographic factors on voter behavior with a negative direction of influence. The findings of this study are expected to contribute to academic development, particularly regarding money politics and voter behavior, in order to minimize the practice of money politics in the future.